(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article discusses the role of the flipped classroom approach in teaching English, particularly the organization of an exercise system based on this model. Unlike traditional instruction, theoretical materials are studied independently before class, while classroom time is devoted to interactive and communicative activities. The article analyzes the stages of pre-class, in-class, post-class activities, and challenges related to implementing the flipped classroom model. The findings demonstrate that the flipped classroom model contributes to the development of communicative competence, learner autonomy, critical thinking, and motivation among students.